Methods of industrial enterprise strategic management: Integration of approaches - Tatyana Yu. Zheleznova; Elena D. Vaisman (Управленец, 2022)
The article aims to develop an integrated method for managing an industrial enterprise highly responsive to the challenges of a changing environment. The theory of the firm, the general theory of management and strategic management theory constitute the methodological basis of the study. The research methods are structural-logical analysis, comparative analysis, and matrixing. We distinguish between three industrial enterprise management methods, based on: (a) complex financial indicators, (b) a balanced scorecard, and (c) a system of continuous improvements. The results of comparative analysis allowed identifying high-potential methods of strategic management. We conclude that it is expedient to integrate various methods, which will level the shortcomings of each of them and, in some cases, help obtain a synergistic effect. The study proposes a mechanism for integrating a balanced scorecard with the Hoshin Kanri tools, which contributes to the development of strategic management theory. The mechanism can be of use for industrial enterprises when formulating their development strategy.